2016
DOI: 10.1152/ajpcell.00319.2015
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial Ca2+ uniporter: regulation by auxiliary subunits and signal transduction pathways

Abstract: Mitochondrial Ca(2+) homeostasis, the Ca(2+) influx-efflux balance, is responsible for the control of numerous cellular functions, including energy metabolism, generation of reactive oxygen species, spatiotemporal dynamics of Ca(2+) signaling, and cell growth and death. Recent discovery of the molecular identity of the mitochondrial Ca(2+) uniporter (MCU) provides new possibilities for application of genetic approaches to study the mitochondrial Ca(2+) influx mechanism in various cell types and tissues. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 124 publications
1
29
0
Order By: Relevance
“…In mammalian cells, suppression of EMRE abrogates MCU-mediated Ca 2ϩ currents demonstrated by mitoplast patch clamp experiment (12,14). However, functional consequences of EMRE overexpression have not been studied yet (44). In our study, EMRE showed a strong genetic interaction with MCU in Drosophila.…”
Section: Drosophila Mcu In Ros-induced Cell Deathmentioning
confidence: 47%
“…In mammalian cells, suppression of EMRE abrogates MCU-mediated Ca 2ϩ currents demonstrated by mitoplast patch clamp experiment (12,14). However, functional consequences of EMRE overexpression have not been studied yet (44). In our study, EMRE showed a strong genetic interaction with MCU in Drosophila.…”
Section: Drosophila Mcu In Ros-induced Cell Deathmentioning
confidence: 47%
“…MCU comprises the pore-forming unit of a complex of proteins that includes regulatory proteins involved in gating of MCU (for review see [325]). The role of MCU-regulated mitochondrial Ca 2+ uptake on maintaining mitochondrial bioenergetics is dependent on the relative metabolic activity of specific tissues, as demonstrated in MCU knockout animals, where loss of MCU has little effect on Oxidative Phosphorylation of mouse embryonic fibroblasts.…”
Section: Redox Regulation Of Er and Mitochondrial Ca2+ Modulatorsmentioning
confidence: 99%
“…The molecular characterization of the uniporter (Baughman et al, 2011, De Stefani, Raffaello et al, 2011, Perocchi et al, 2010, Plovanich et al, 2013, as well as a number of accessory proteins, i.e., MICU1, 2, 3 and EMRE (Perocchi et al, 2010, Plovanich et al, 2013, Sancak et al, 2013 opened the possibility of genetic manipulation of the components of the uniporter (Jhun et al, 2016). It was shown that silencing of Mcu abrogates the rise in [Ca 2+ ] mito and the cytosolic ATP/ADP ratio in response to glucose in mouse -cells (Tarasov, Semplici et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial Ca 2+ uptake in most cells occurs via a macromolecular protein complex, known as the calcium uniporter holocomplex (Jhun, Mishra et al, 2016, Sancak, Markhard et al, 2013. MCU forms the central pore-forming subunit of the complex, while MCU regulatory subunit b (MCUb), essential MCU regulator (EMRE), mitochondrial uptake 1 and 2 (MICU1 and MICU2) form the accessory components (Kamer & Mootha, 2015).…”
Section: Introductionmentioning
confidence: 99%